Rancang Bangun Aplikasi Pengenalan Pupuh Bali Menggunakan Metode Mel Frequency Cepstral Coefficients - I Dewa Gede Budi Dharma Prabhawa; Duman Care Khrisne; Made Sudarma (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2019)
Pupuh is a basic of Tembang for someone that can later be used for further learning to a higher level that is Sekar Madya and Sekar Agung. Balinese culture is an important feature to determine the ethnicity identity of a group. Then it should be the Balinese use and preserve Pupuh that has been inherited by the ancestors. The media for Balinese Pupuh learning will be using an Android device with MFCC method. To attract the interest of young peoples to learn Balinese Pupuh, then this Balinese Pupuh learning system based-Android was created. This application will use the sound recorded by Android devices and sent to the Python server for systematic calculations, then returned to the Android devices and will get the correct or wrong answer which according to server calculation. By developing this Balinese Pupuh learning system, expected can help the teachers or Balinese language teachers to teach their students about Balinese Pupuh on a mobile and practical.